Control theory : a guided tour - Leigh, J. R. (IET control engineering, 2012)
The book reviews developments in the following fields: control theory; control design; Laplace transform; frequency response methods; mathematical modelling; nonlinear systems; stability; discrete time control systems; digital control system; multivariable linear systems; state space approach; optimisation; state estimation; and robust control design.